The Role of Farmer Groups in Increasing the Efficiency of Post-Harvest Handling of Chilies in Baho Village - La Oge; La Panga; Wd Syafitri Salsabila (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Post-harvest handling is a crucial stage in maintaining the quality and market value of agricultural commodities, including chili peppers, which are one of the main products of the community in Baho Village. This study aims to analyze the role of farmer groups in improving the efficiency of chili post-harvest handling in Baho Village, as well as to identify factors that support or hinder the implementation of optimal post-harvest practices. This research employs a descriptive qualitative approach using in-depth interviews, field observations, and documentation with farmer group members and village officials. The results indicate that farmer groups play a significant role in coordinating harvesting, drying, sorting, and packaging processes. Through training activities and experience sharing, farmer groups enhance members’ skills in maintaining crop quality and reducing product damage. However, challenges include limited storage facilities, lack of access to modern post-harvest technology, and market price fluctuations that affect farmers’ motivation. With support from local government and extension agencies, optimizing the role of farmer groups is expected to improve post-harvest efficiency and the welfare of chili farmers in Baho Village.